Anterior Cervical Arachnoid Cyst in A Child: A Case Report - Arman, DM; Ekramullah, Sheikh Muhammad; Mukherjee, Sudipta Kumer; Ahmed, Misbahuddin; Mia, MA Quddus; Huq, Naila (Journal of National Institute of Neurosciences Bangladesh, 2018)
Intradural arachnoid cysts involving the spine are uncommon and especially rare in an anterior cervical location. In the literature, among 15 patients, 8 were in the paediatric age group and in 3 patients the cyst was localized to the full length of the cervical spinal canal. Although they occur secondary to trauma, haemorrhage, surgery or inflammation, most of them are known to be idiopathic or congenital. Although the disease shows a dramatic neurological course, early diagnosis and treatment could provide good results. In the paediatric age group, cervical anterior intradural arachnoid cyst is an unusual cause of quadriparesis. The rarity of this condition and the relevance of MRI in the accurate and early diagnosis is discussed here. A 4 year-old girl with a intradural arachnoid cyst extending from C4 to C7 situated anteriorly is reported here; diagnosis and treatment modalities are discussed. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 52-56